Teachers' Competency Management Strategies in Improving The Character of Students Who Are Ready to Lead and Ready To Be Led By Pesantren - Masruroh, Waqiatul (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Pesantren is an Islamic educational institution in Indonesia with characteristics and an educational system that is different from other formal education. One of the proofs of the difference is about improving the character of being ready to lead and ready to be led with the nuances of Islamic teachings. This research is categorized in the form of descriptive qualitative research with the type of field research. To obtain relevant data in this study. The researcher used three data collection techniques, namely observation, interview, and documentation. Meanwhile, the analysis uses data reduction, data presentation, and data verification. So in the study, a conclusion was obtained that the teacher's competency strategy in fostering character is ready to lead and ready to be led by externalization, objectivity, and internalization. Meanwhile, activities that help in improving this character are student group leadership training, leadership and management training, basic scouting advanced courses, and student organizations. Also, the supporting and inhibiting factors are because there are strengths and opportunities, as well as weaknesses and challenges.